Global Trade Dynamics: The Effects of Tariffs and Trade Agreements on International Business - Amina Jahan; Tariq Al-Harbi (International Journal of Economics, Commerce, and Management, 2024)
This article analyzes the effects of tariffs and trade agreements on global trade dynamics and international business operations. By reviewing recent trade policies and their implications for various industries, the study highlights how tariffs influence supply chain decisions and market entry strategies. The findings provide recommendations for businesses navigating the complexities of international trade in a protectionist environment.